Exploring the Foundations of Islamic Education: Insights from Ibn Sina and Ibn Khaldun - Mohammad Sabarudin; Ibnu Imam Al Ayyubi; Rifqi Rohmatulloh; Irfan Suryana; Tommy Tanu Wijaya (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Education is the application of philosophy and cannot be separated from one another. Education and philosophy are crucial in human life, including in Islamic education. Islamic education refers to the educational system and practices based on Islamic principles and values. The perspectives of Islamic education are motivated by various thoughts of Islamic figures and scientists sourced from the Qur'an. This study aims to explore the foundations of Islamic education according to Ibn Sina and Ibn Khaldun's perspectives and to show whether or not the perspectives can complete each other and are still relevant to education nowadays. The method used is a literature study with a qualitative approach. The data were presented as descriptive data based on the analysis of Ibn Sina and Ibn Khaldun from various sources, including documents and texts. The results show that Ibn Sina and Ibn Khaldun's perspectives have a specific pattern that complements each other and can be expanded in the modern era.